THE EFFECT OF COOPERATIVE LEARNING MODEL TYPE GROUP INVESTIGATION TOWARD STUDENT LEARNING OUTCOMES ON CIRCULAR MOTION AT X SMA NEGERI 18 MEDAN ACADEMIC YEAR 2018/2019 - Rio Mahera Lumbantoruan; Derlina Nasution (INPAFI (Inovasi Pembelajaran Fisika), 2020)
The purpose of this research was to know how student learning outcomes using cooperative learning model type group investigation toward student learning outcomes on circular motion at X SMA Negeri 18 Medan Academic Year 2018/2019. This research used a quasi experiment method with the design of two Pretest and Posstest groups. The population in this study were all students of class X consisting of six classes. In the study sample selected two classes with random techniques, obtained class X MIA 3 as the experimental class and X MIA 6 as the control class with a total of 35 students. And this research uses instruments, namely 20 multiple choice questions. The results of the data obtained are pretest for experiment class and control class is experimental class bigger than control class. Then the normality and homogeneity tests are normally distributed and homogeneous. So it can be said that the initial abilities in both classes are the same. The result posttest for experiment class and control class is experiment class bigger than control class. The results of the t test one tail showed that there were significant differences due to the effect of cooperative learning model type group investigation on student learning outcomes.Keywords: Group Investigation, Learning Outcomes, Regular Motion